Synthesis of novel photochromic pyrans via palladium-mediated reactions - Böttcher, Christoph; Zeyat, Gehad; Ahmed, Saleh A.; Irran, Elisabeth; Cordes, Thorben; Elsner, Cord; Zinth, Wolfgang; Rueck-Braun, Karola (Beilstein Journal of Organic Chemistry, 2009)
Photochromic pyrans for applications in material and life sciences were synthesized via palladium-mediated cyanation, carbonylation and Sonogashira cross-coupling starting from bromo-substituted naphthopyran 1 and benzopyrans 2a/b. A novel photoswitchable benzopyran-based ω-amino acid 6 for Fmoc-based solid-phase peptide synthesis is presented. The photochromic behaviour of the 3-cyano-substituted benzopyran 5a was investigated by time-resolved absorption spectroscopy in the picosecond time domain.
Keywords: benzopyrans; chromenes; naphthopyrans; palladium-mediated coupling reactions; photochromism